The Influence of the TikTok Algorithm on Gen Z's Language Ability - Puspasari, Karirah Dwi; Rahmawati, Dwi; Hanifah, Ratna Laylatul; Agustin, Natasya Jollyn Karisya; Amalia, Syakira KHusnul; Shobayarin, Endang (International Journal on Advanced Science, Education, and Religion, 2024)
This research aims to (1) To find out the language used by Gen Z before and after using Tiktok. (2) To determine the positive and negative impacts of the TikTok algorithm in shaping the language skills of Gen Z. The research method used is a qualitative method, collecting data using indirect interviews via Google Form which are distributed to informants who are active TikTok users. Carried out from October to November. The collected data was then analyzed descriptively. The results of this research show that (1) The language used by Gen Z before using TikTok tends to be informal, everyday and does not use a lot of slang or slang originating from TikTok. (Dewi, 2024) After using the TikTok application, the language used by Gen Z is also I still tend to be informal on a daily basis, but I use a lot of slang or slang that comes from Tiktok (2) Positive impact The TikTok algorithm in shaping Gen Z's language skills is increasing language creativity and the ability to adapt to various communication styles. Meanwhile, the negative impact is a decrease in Gen Z's use of standard language and an increase in the use of informal words, which can affect language skills in formal contexts.